'The Bell Curve' in Perspective Race, Meritocracy, Inequality and Politics - Tucker, William H. (Palgrave Studies in the Theory and History of Psychology,, 2024)
"Within the vast literature around race/class and IQ this book stands out as an original contribution. It makes an empirical argument about the vast economic inequality that Murray and others say is inevitable and natural but is, in reality, the result of political and social choices. The topic is both old and exceptionally timely. This book is a final and fitting entry for this exceptional scholar and should be read by historians, psychologists, political scientists, sociologists, and economists." -John P. Jackson Jr., Adjunct Professor of History at Michigan State University, USA, and co-author of Darwinism, Democracy and Race "By demonstrating how The Bell Curve was clearly a social policy document that aimed to reshape society and eliminate social programs, Tucker provides an important new analysis of the interplay of science and politics, one informed by his lifelong commitment to social justice." - From the Foreword byAndrew S. Winston, Professor Emeritus of Psychology, University of Guelph, Canada This open access book examines the implications of The Bell Curve for the social, economic, and political developments of the early 21st century. Following a review of the reception of The Bell Curve and its place in the campaign to end affirmative action, Professor Tucker analyses Herrnstein's concept of the "meritocracy" in relation to earlier 20th century eugenics and the dramatic increase in economic inequality over the past 30 years. Tucker demonstrates how, contrary to The Bell Curve's predictions, the reallocation of these huge sums was neither rational nor beneficial for society. The book moves on to situate The Bell Curve within contemporary politics and shows how it can be seen to have played a role in the 2016 US election. This compelling analysis will appeal to scholars and those with an interest in the history of scientific racism, the history of psychology and the sociology of knowledge and science. William H. Tucker (1940-2022) was Emeritus Professor of Psychology at Rutgers University, Camden, USA. He was the author books including: The Cattell Controversy: Race, Science, and Ideology (2009), The Intelligence Controversy (2005), The Funding of Scientific Racism (2002), and The Science and Politics of Racial Research (1994). Professor Tucker sadly died before publication could be completed. This work has been prepared for publication by his colleague Professor Daniel Hart with the permission of his widow Monica Drozd.